(untitled) (The Batuk, 2026)
Motivating customers to choose an online platform repeatedly has become increasingly important as digital shopping continues to expand. This study investigates the determinants of online retail patronage intentions by integrating Uses and Gratifications Theory (UGT), Self-Determination Theory (SDT), and key behavioral factors, while examining the moderating effect of generational chores (Gen Z vs. Gen Y). The study adopted quantitative approach and cross-sectional survey design to collect data from 390 online shoppers, purposively and conveniently selected respondents. Using Confirmatory Factor Analysis (CFA), Structural Equation Modeling (SEM), and Multigroup Analysis (MGA), the study revealed behavioral factors: trust, customer experience, perceived value, and social & environmental responsibility, as the strongest predictors of patronage intentions. The results also show the significant influence of UGT and SDT motivations on the intentions, though with varying strengths. The study suggests that Gen-Z uniquely enjoys the digital environments to fulfill psychological needs in comparison to Gen-Y; however, the generational differences emerge not merely from age-based digital familiarity but also from varied exposure to technological and cultural transformations. The study contributes to digital consumer behavior literature and provides actionable insights for retailers to tailor strategies across generational segments.